NUMERICAL APPROACH TO DETERMINING THE RESONANT FREQUENCIES OF WIND TURBINE POLES (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
The study presents an approach based on 3D numerical methods for estimating the resonant frequencies of the mast of a wind turbine. This system comprises components that operate on electromechanical principles that are sources of mechanical oscillations. The FreeCAD environment is used to create geometries with complex structures, and the MATLAB environment is used to perform the numerical study specific to mechanical analysis. A comparison with experimental data is carried out for a given configuration to validate the method.
Keywords: Resonance frequencies; 3D numerical methods; Wind Turbines